Modelıng And Optımızatıon Of Teacher Professıonal Commıtment Strengthenıng - Heriyanto Heriyanto; Soewarto Hardhienata; Oding Sunardi (Cita Konsultindo Research Center, 2024)
This research focuses on modeling and optimizing teacher professional commitment strengthening through a comprehensive research methodology encompassing preliminary, qualitative, and quantitative stages. The study employs a combination of qualitative and quantitative methods, including the POP-SDM method, to develop a theoretical model and hypotheses. Data collection involves surveys, interviews, and questionnaires among school principals and experienced teachers. The study spans from October 2022 to July 2024, with data collected from 16 boarding high schools in Sukabumi Regency, West Java Province. The results reveal significant insights into various variables influencing teacher professional commitment, including empowerment, servant leadership, personality, quality of work life, and job satisfaction. Descriptive statistical analyses demonstrate high levels of commitment, empowerment, servant leadership, personality traits, work-life quality, and job satisfaction among respondents. Structural equation modeling (PLS-SEM) is employed to construct and evaluate variable constructs, assess path coefficients, and test hypotheses. The model demonstrates strong predictive power and significant direct and indirect effects on teacher professional commitment. Overall, the findings suggest that factors such as empowerment, servant leadership, personality, quality of work life, and job satisfaction significantly influence teacher professional commitment. The study provides insights for educators and policymakers to enhance teacher commitment through targeted interventions, focusing on areas identified for improvement based on expert assessments and statistical analyses.